From the editor's desk: "communiversity" as a portmanteau - Zamri, Zahid (Centre for Islamisation (CENTRIS), IIUM, 2024)
The word “communiversity” is a portmanteau. It is the combination between “community” and “university.” One of the purposes of a portmanteau is to solidify the meanings of two different but interrelated words into one word to show its significance and uniqueness in the realm of language.